Syntheses of dipeptide alcohols and dipeptide aldehyde precursors catalyzed by plant cysteine peptidases - Morcelle del Valle, Susana Raquel (2013)
Two different cysteine peptidases obtained from plant latex (papain from Carica papaya and araujiain from Araujia hortorum) demonstrated to be good catalysts for the condensation of coded and non-coded Cbz-amino acids and amines such as amino alcohols and amino acetals in acetonitrile containing 1% (v/v) water. Both kinetically and thermodynamically controlled syntheses were proved. Thermodynamic approach was selected since the conversions in product found were similar to those obtained by the kinetic approach; furthermore, a minor number of synthetic steps were needed. For the Cbz-amino acids tested, conversions were higher than 80% at 48–72 h of reaction, except for the Phg derivative, which produced conversions of ca. 40 and 20% for papain and araujiain, respectively. Product yields for the scaled up reactions were similar to the conversions obtained in microscale synthesis. The flexibility of both enzymes for the nucleophile allowed the condensation reaction of Cbz-Ala-OH with an amino diacetal derivative. The resulting dipeptide diacetal derivative can be easily tranformed into a dipeptide aldehyde by acid hydrolysis.